REVIEW OF STATCOM IN GUIDING THE GRID CONNECTED WIND ENERGY FOR POWER QUALITY ENHANCEMENT - GHADAGE MOHINI S.,; PROF. KINGE A. P, (International Journal of Innovations in Engineering Research and Technology, 2021)
There is a problem with the different quality of electricity due to the use of renewable energy, one of which is the power of the wind. Infusion of a wind farm into the grid affects the quality of electricity. According to the guidelines established by the International Electro technical Commission, IEC -61400 standards, the performance, and electricity quality of the wind turbine are determined based on the measured values and follows the rules. The resultof the wind turbine on the grid system of the power quality measurement is the electrical behavior of active power, reactive power, voltage change, and flicker, harmonic and switching operation, guidelines measured according to domestic/international. Paper investigations highlight the problem of electric quality in the installation of wind turbines on the grid cause grid. In this proposed design, the static compensator (STATCOM) is connected to the common connection point of common couplingwith a battery energy storage system (BESS) which alleviates the problem of electric quality. The battery case is integrated to maintain the actual source of variable leeward energy. In order to improve the quality of the electricity, the STATCOM control plan of the wind-powered system connected to the network. The effectiveness of the proposed method reduces the reactive power demands of the load and the main power supply of the induction generator. It is planned to present development of network coordination rules and to improve power quality specifications by IEC network.